Jung on art : the autonomy of the creative drive - Van den Berk, Tjeu (Routledge, 2012)
In this book, Tjeu van den Berk examines C.G. Jung's personal perspective on art and how his work intensely engages with this theme. It analyses Jung's profound reflections on artistic considerations such as how we experience art, the specific qualities in the perception of beauty, the nature of the creative process and the aesthetic attitude. Jung on Art considers Jung's feelings about art simply being 'art' rather than reducing it to a moral, political, religious or psychological product. It also discusses Jung's notion that the artist is only a breeding ground for a piece.